2020
DOI: 10.3390/microorganisms8111631
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Microbial Community Structures along a Meandering River

Abstract: Streams and rivers convey freshwater from lands to the oceans, transporting various organic particles, minerals, and living organisms. Microbial communities are key components of freshwater food webs and take up, utilize, and transform this material. However, there are still important gaps in our understanding of the dynamic of these organisms along the river channels. Using high-throughput 16S and 18S rRNA gene sequencing and quantitative PCR on a 11-km long transect of the Saint-Charles River (Quebec, CA), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
2
8
0
Order By: Relevance
“…Furthermore, our results from microbial source tracking also suggest a minor contribution of subsurface environments to river communities through groundwater discharge. These results are consistent with previous study by Villeneuve et al [30].Our results also confirmed that most of the bacterial diversity for river was attributed to unknow sources which can be explained by rapid changes in community composition as a result of water transit [41].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results from microbial source tracking also suggest a minor contribution of subsurface environments to river communities through groundwater discharge. These results are consistent with previous study by Villeneuve et al [30].Our results also confirmed that most of the bacterial diversity for river was attributed to unknow sources which can be explained by rapid changes in community composition as a result of water transit [41].…”
Section: Discussionsupporting
confidence: 93%
“…The same taxa that we identified as being relatively abundant above resurfaced when we calculated the core microbiome for each shop type (taxa found in >50% of samples per shop type at abundance >0.1%). We identified seven dominant core ZOTUs (Dawson et al , 2017; Cruaud et al , 2020) shared between all shop types, attributed to the genera: Corynebacterium , Propionibacterium , Pseudomonas , Streptococcus (n = 2) and Staphylococcus (n = 2) (Fig. S2; detection threshold = 0.001, prevalence threshold = 0.5; Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…The linked map contains the symbols for all shops in a town from which banknotes were collected. (Dawson et al, 2017;Cruaud et al, 2020) Due to the size of the file this table is available separately (suppTable_08.csv).…”
Section: Supplementary Tablesmentioning
confidence: 99%